2017
DOI: 10.18203/2319-2003.ijbcp20170812
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization pattern in dermatology outpatient department at a tertiary care hospital in Navi Mumbai

Abstract: Background: Skin diseases are common and cause a huge disease burden globally. Different class of drugs and combinational products are available in dermatology for treatment. Periodic prescription analysis in the form of drug utilization study can improve the quality of prescription and curb the menace of irrational prescribing. Aim and objective of the study were to study the prescribing pattern and drug utilization trends in Dermatology outpatient department at a tertiary care hospital in Navi Mumbai. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
2
5
2
Order By: Relevance
“…In this research, percent encounters with an antibiotic prescribed were 13%. Similar data was found in study of 19 (11.07%) where it was higher than our study 18 (28.61%). Antibiotics were most commonly prescribed class of drugs 22,5 and.…”
Section: Who Core Prescribing Indicatorsupporting
confidence: 92%
See 3 more Smart Citations
“…In this research, percent encounters with an antibiotic prescribed were 13%. Similar data was found in study of 19 (11.07%) where it was higher than our study 18 (28.61%). Antibiotics were most commonly prescribed class of drugs 22,5 and.…”
Section: Who Core Prescribing Indicatorsupporting
confidence: 92%
“…18 Average number of drugs per prescription was nearly equal to 3.27, the value obtained in the study of. 19 Average number of drugs per prescription was 3.73 in the study of 20 which is higher than what was observed in our study. Average number of drugs prescribed per patient encounter is high in comparison to optimal value in the range of 1.6-1.8 21 and hence our study suggests that the number of drugs prescribed per patient is more than what suggested by WHO.…”
Section: Who Core Prescribing Indicatorcontrasting
confidence: 75%
See 2 more Smart Citations
“…In a study done by Patil et al showed male were affected 56.86% followed by the female 43.14%. 10 In George et al study also most commonly male (51.35%) were affected followed by female. 11 Dermatophytosis can affect every age group with no specific age group being immune to the infection.…”
Section: Discussionmentioning
confidence: 84%